Whistleblowing and fraud in digital era - Santi Widhiyanti; Yustrida Bernawati (STIE Perbanas Surabaya, 2020)
This article discusses whistleblowing and fraud in the digital era in Indonesia using a literature study. Digital whistleblowing allows someone to reveal a number of information accompanied by photos/ videos through social media/ other online sources. This information is investigated further to find out if there is fraud after checking the truth, because there is a possibility that the information is inaccurate. The absence of a checking process and confirmation of its truth causes inaccurate information. The case that occurred in one of the SOEs in Indonesia initially emerged from a tweet on a Twitter account which was finally able to uncover the alleged fraud in terms of abuse of office. This is an example of the role of technology in digital whistleblowing and fraud. Digital technology can detect if there is a change in the softcopy file through the recorded digital footprint and then submit it to the authorities so that they can track the identification of previous users related to the possibility of document leakage. Artificial Neural Network (ANN) which is part of artificial intelligence (AI) technology can be used to detect fraud. ANN is a system that is able to process complex amounts of data through pattern recognition. There has been much discussion about the use of information technology in Indonesia, but the use of ANN has not been much discussed.